Comparing dust flux records from the Subarctic North Pacific and Greenland: Implications for atmospheric transport to Greenland and for the application of dust as a chronostratigraphic tool. (2nd June 2015) - Serno, Sascha; Winckler, Gisela; Anderson, Robert F.; Maier, Edith; Ren, Haojia; Gersonde, Rainer; Haug, Gerald H.
Abstract We present a new record of eolian dust flux to the western Subarctic North Pacific (SNP) covering the past 27, 000 years based on a core from the Detroit Seamount. Comparing the SNP dust record to the North Greenland Ice Core Project (NGRIP) ice core record shows significant differences in the amplitude of dust changes to the two regions during the last deglaciation, while the timing of abrupt changes is synchronous. If dust deposition in the SNP faithfully records its mobilization in East Asian source regions, then the difference in the relative amplitude must reflect climate‐related changes in atmospheric dust transport to Greenland. Based on the synchronicity in the timing of dust changes in the SNP and Greenland, we tie abrupt deglacial transitions in the 230Th‐normalized 4He flux record to corresponding transitions in the well‐dated NGRIP dust flux record to provide a new chronostratigraphic technique for marine sediments from the SNP. Results from this technique are complemented by radiocarbon dating, which allows us to independently constrain radiocarbon paleoreservoir ages. We find paleoreservoir ages of 745 ± 140 years at 11, 653 year B.P., 680 ± 228 years at 14, 630 year B.P., and 790 ± 498 years at 23, 290 year B.P. Our reconstructed paleoreservoir ages are consistent with modern surface water reservoir ages in the western SNP. Good temporal synchronicity between eolian dust records from the Subantarctic Atlantic and equatorial Pacific and the ice core record from Antarctica supports the reliability of the proposed dust tuning method to be used more widely in other global ocean regions.